Motivational factors and satisfaction of police personnel in Bansalan, Davao del Sur - Caca, John Paul G.; Responso, Romeo S.; Verana, King Andrew O.; Malmis, Michael Jay O. (--Davao del Sur: UM Bansalan Collge, 2015)
This study was conducted to determine the level of motivational factors and satisfaction of police personnel in bansalan police station. Using the descriptive-correlation method of research by which the researchers personally administered the question to the police personnel with the sample size of 55 participants as respondents resulted to data gathered and findings determined that the level of motivational factors 4.70 is very high and satisfaction 4.68 is very high of police personnel in terms of feeling valued, achievement, and work relationship, work itself and pay and condition is very high. The over r-value is 0.908 or significant for the p-value is lower than 0.05 alpha level. Such resulted that there is a significant correlation between the level of motivational factors and the satisfaction of the police personnel in dispense of thier performance. recommendation is for the senior officers to continue to motivating vis a vis guiding the new personnel for more and better performance. Likewise, police officers to look for other opportunities to give better services to the community.